Postural alignment and muscle extensibility assessment's by the SARROMM scale in children and teenagers with Cerebral Palsy (Research, Society and Development, 2021)
Justification: Cerebral Palsy (CP) is characterized by a brain lesion in the phase of its structuring and maturation. Affected individuals present alterations that cause postural maladjustments, generating a deficit in movement. SAROMM is a scale that assesses individuals with CP, identifying postural changes, spinal alignment, muscle extensibility and range of motion. Objective: To assess postural alignment and muscle extensibility in children and adolescents with CP using the SAROMM scale. Methods: The observational cross-sectional study was carried out in a virtual environment for the application of the SAROMM scale, with an average evaluation time between 15 and 30 min. Results: The final sample consisted of 8 children, predominantly male (62.5%) and diplegia, the most common topographic diagnosis (62.5%). Regarding postural alignment, it was identified that 37.5% had a minimum score of 0, indicating the absence of alignment limitations with active correction. In the section on muscle extensibility, by joint, it was observed that patient VI obtained a score of 0, demonstrating no changes detected in this assessment, while patient IV exhibited the highest value in lower limb scores, demonstrating more compromise than the others. Conclusion: The assessed children who had low scores in the score had voluntary motor skills such as sitting, walking, rolling and crawling at the expense of those who do not have these skills and obtained higher scores.